The Effect of Intellectual Capital and Good Corporate Governance on Company Value Mediated by Competitive Advantage - Selvia Roos Ana; Agung Budi Sulistiyo; Whedy Prasetyo (Journal of Accounting and Investment, 2021)
Research aims: This research aims to analyze the effect of intellectual capital and good corporate governance on company value by using competitive advantage as a mediation on companies listed on the Corporate Governance Perception Index from 2014 to 2018.Design/methodology/approach: This research used nine companies from the Corporate Governance Perception Index as a sample listed during the 2014-2018 period. The analysis methods of this research were Multiple Linear Regression and path analysis.Research findings: The research revealed that the company's competitive advantage could increase the company value but could not mediate company value. However, competitive advantage is inseparable from the role of intellectual capital and good corporate governance.Theoretical contribution/Originality: This study provides a theoretical contribution to determining company value using competitive advantage as mediation. Besides, this research confirms the resource-based theory that the company can win the competition by having a competitive advantage to increase company value. Hopefully, these findings can give a comprehensive picture for the company.Practitioner/Policy implication: The results of this study are expected to provide an overview to management and investors that intellectual capital has not been able to increase company value because intellectual capital is still a hidden value that has not been able to attract investors' attention to how beneficial intellectual capital is for the company. Besides, this study also showed that the implementation of Good Corporate Governance is not just a formality but must become an organizational culture to encourage increased company value.Research limitation/Implication: This study was only conducted on companies listed on the Corporate Governance Perception Index from 2014 to 2018. Therefore, the generalizability of this study is limited